Poly Acrylamide Gel Electrophoresis of Serum Protein, Application to Kala-azar Patients - Nada M.T. Al-Bashir (College of Pharmacy University of Baghdad, 2017)
Sera samples were collected from 60 children aged 4-60 months, all were clinically and serologically proven cases of visceral leishmaniasis, as well as  from 10 healthy children, all were seronegative with no history of parasitic infection who serve as a control during the study. Serum total protein and albumin were measured and compared between the control and visceral leishmaniasis patients. Serum protein profiles have been investigated using the conventional sodium dodecyl sulphate â€" polyacrylamide gel electrophoresis (SDS-PAGE).  Serum of control group showed the specific protein pattern with five protein bands, while serum protein profile in visceral leishmaniasis patients revealed three groups of electrophoretic banding patterns.  , 50% showed twelve bands, 36.66% of the patients showed nine bands and 13.33% showed ten bands. At least four of these bands were found to be common among the infected groups which may be of diagnostic value and required further investigations. The three different electrophoretic patterns groups may be correlated with the previous epidemiological observations in respect of different clinical presentation of the disease and different response the chemotherapeutic agents at many endemic areas around the world. Key words: Protein band, protein patterns, serum protein, sodium dodecyl sulphate-poly acrylamide gel electrophoresis (SDS-PAGE), visceral leishmaniasis.